Pengaruh Akupresur Titik LI4 Dan SP6 Terhadap Penurunan Dismenore Pada Remaja - Arini Novilia Nur Khasanah; Kamidah Kamidah (Jurnal Anestesi, 2023)
Background: Dysmenorrhea is pain that occurs in the lower abdomen experienced by women approaching menstruation and during menstruation. As a result of dysmenorrhea can cause discomfort that can interfere with adolescent activities.Overcoming dysmenorrheal pain, namely with acupressure. The acupressure points used are LI4 and SP6 points. Emphasis on the hegu point (LI4) has a strong function on the mind so that it can be used in calming the mind and reducing anxiety, because dysmenorrhea can be caused by stress and psychological disorders while the SP6 point has a function to strengthen the spleen, restore Yin balance in the liver and kidneys so that it can improve blood circulation thus the SP6 point can reduce dysmenorrheal pain. Objective : To determine the effect of LI4 and SP6 point acupressure on reducing dysmenorrheal in adolescent. Method : This type of research uses a pre-experimental method with a one group pre-test post-test design. The sample obtained is from the calculation of the slovin formula, namely as many as 30 people. Results : The results of the study with the Wilcoxon Signed Rank test obtained a p value of 0,000 where the value is smaller a (0,005) meaning that there is an effect of acupressure.